2014
DOI: 10.1515/jbcpp-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid inhibits DMH-induced cell proliferation in experimental rats

Abstract: The above findings clearly underline the chemopreventive efficacy of RA against DMH-induced colon carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Doolaege, et al reported that 64.3 mg/kg (193.43 mM) CA orally administered to rats resulted in a plasma concentration of 0.015 mg/mL (45.12 μM) [116]. Another study reported that ingestion of 360 mg/kg/day RA after 8 weeks resulted in a plasma concentration of 1.1 μM [117]. The reported plasma concentrations of CA, carnosol and their metabolites were in the micromolar range indicating that absorption and bioavailability are likely not barriers for these components of RE [114,115,118].…”
Section: Dosage and Bioavailabilitymentioning
confidence: 99%
“…Doolaege, et al reported that 64.3 mg/kg (193.43 mM) CA orally administered to rats resulted in a plasma concentration of 0.015 mg/mL (45.12 μM) [116]. Another study reported that ingestion of 360 mg/kg/day RA after 8 weeks resulted in a plasma concentration of 1.1 μM [117]. The reported plasma concentrations of CA, carnosol and their metabolites were in the micromolar range indicating that absorption and bioavailability are likely not barriers for these components of RE [114,115,118].…”
Section: Dosage and Bioavailabilitymentioning
confidence: 99%
“…Recent studies have revealed that RA possessed antioxidant, anti-inflammatory, and anti-angiogenic effects [34]. Furthermore, accumulating evidence indicates that RA has anti-tumor effects by inhibiting tumor cell growth [5]. Our previous studies showed that RA had anti-tumor effects in the H22 -xenograft models with little toxicity effects and the mechanism involved inhibition of inflammatory cytokines and NF-κB p65 pathway in the tumor microenvironment [6].…”
Section: Introductionmentioning
confidence: 99%
“…The phase II enzymes, including glutathione S-transferase (GST) and DT-diaphorase (DTD) detoxify the electrophilic intermediates [ 17 , 18 ]. The quantitative evaluation of argyrophilic nucleolar organizing regions (AgNORs) determines the rate of cell proliferation and their numbers can reflect the prognosis of colon cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%